Pengaruh Kepemimpinan pendidikan, Lingkungan belajar, Suasana belajar terhadap Peningkatan produktivitas belajar dengan variabel antara motivasi belajar pada semester VIII Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Alamsyah, Anas Amin (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
The purpose of this study are: 1) To know and analyze the influence of Educational Leadership on motivation to learn. 2) To know and analyze the influence of learning environment on learning motivation. 3) To know and analyze the influence of learning atmosphere on learning motivation. 4) To know and analyze the influence of Educational Leadership on improving learning productivity. 5) To know and analyze the influence of the learning environment on improving learning productivity. 6) To know and analyze the influence of learning atmosphere on improving learning productivity. 7) To know and analyze the influence of learning motivation to improve learning productivity. 8) To know and analyze the direct influence of Educational Leadership, Learning Environment and Learning Atmosphere on improving learning productivity through variables between learning motivation. Based on the consideration of time, energy, and funds, as well as the scope of the problem and the number of subjects in a population of 53 people, this study used census research. Where all members of the population sampled From the results of the study can be summarized as follows: 1) Educational leadership has no significant effect on learning motivation. 2) Learning environment has a significant effect on learning motivation. 3) Learning atmosphere has a significant effect on learning motivation. 4) Educational leadership has a significant effect on the increase of learning productivity. 5) Learning environment has a significant effect on the increase of learning productivity. 6) The learning atmosphere has no significant effect on the increase of learning productivity. 7) Learning motivation has no significant effect on the increase of learning productivity. 8) Educational leadership, learning environment and learning atmosphere each directly affect the improvement of learning productivity through the variables between learning motivation.